A confidential enquiry into cases of neonatal encephalopathy. Issue 3 (1st November 2002) - Draper, E S; Kurinczuk, J J; Lamming, C R; Clarke, M; James, D; Field, D
Abstract : Objectives: To assess the quality of care and timing of possible asphyxial events for infants with neonatal encephalopathy; to compare the quality of care findings with those relating to the deaths from the Confidential Enquiry into Stillbirths and Deaths in Infancy (CESDI); and to assess whether the confidential enquiry method is a useful clinical governance tool for investigating morbidity. Design: Independent, anonymised, multidisciplinary case reviews. Setting: Trent Health Region, UK. Patients: All cases of grade II and III neonatal encephalopathy born in 1997, excluding those due to congenital malformation, inborn error of metabolism, or infection. All CESDI deaths thought to have resulted from intrapartum asphyxia in 1996 and 1997. Main measures: Quality of care provided, timing of possible asphyxial episodes, and the source and timing of episodes of suboptimal care. Results: Significant or major episodes of suboptimal care were identified for 64% of the encephalopathy cases and 75% of the deaths. An average of 2.8 and 2.5 episodes of suboptimal care were identified for the deaths and encephalopathy cases respectively. Over 90% of episodes involved the care provided by health professionals. Results were fed directly back to the units concerned on request and changes in practice have been reported. Conclusions: The findings were very similar for the encephalopathy cases and the deaths. We have demonstrated that with minor adaptations the CESDI process can be applied to serious cases of morbidity. However, explicit quality standards, control data, and a more formal mechanism for the implementation of findings would strengthen the confidential enquiry process as part of clinical governance.